ANALISIS PAJAK HIBURAN, PAJAK HOTEL, PAJAK RESTORAN, PAJAK REKLAME TERHADAP PENDAPATAN ASLI DAERAH KOTA MALANG - Ikung, Lasarus; Hama, Aloisius (JURNAL ILMIAH EDUNOMIKA, 2024)
This research aims to determine the effect of entertainment tax, hotel tax, restaurant tax and advertising tax on local revenue n Malang City. The type of research used s quantitative research using secondary data obtained from the Malang City Central Statistics Agency and the Malang City Regional Financial Agency Performance Accountability Report. The sampling technique n this research s the Saturated Sample Technique using the entire population obtained. Hypothesis testing n this research uses a multiple linear regression model. The research results show that Entertainment Tax, Hotel Tax, and Advertisement Tax have an nfluence and contribute to Regional Original ncome n Malang City. Meanwhile, Restaurant Tax has no effect and does not contribute to Original Regional ncome n Malang City.